Objective assessment of dermal fibrosis in cutaneous scarring, using optical coherence tomography, high‐frequency ultrasound and immunohistomorphometry of human skin. (2nd June 2019) - Ud‐Din, S.; Foden, P.; Stocking, K.; Mazhari, M.; Al‐Habba, S.; Baguneid, M.; McGeorge, D.; Bayat, A.
Summary: Background: Noninvasive quantitative assessment of dermal fibrosis remains a challenge. Optical coherence tomography (OCT) and high‐frequency ultrasound (HFUS) can accurately measure structural and physiological changes in skin. Objectives: To perform quantitative analysis of cutaneous fibrosis. Methods: Sixty‐two healthy volunteers underwent multiple sequential skin biopsies (day 0 and 1–8 weekly thereafter), with OCT and HFUS measurements at each time point supported with immunohistomorphometry analysis. Results: HFUS and OCT provided quantitative measurements of skin thickness, which increased from uninjured skin (1·18 and 1·2 mm, respectively) to week 1 (1·28 mm, P = 0·01; 1·27 mm, P = 0·02), and compared favourably with haematoxylin and eosin. Spearman correlation showed good agreement between techniques ( P < 0·001). HFUS intensity corresponded to dermal density, with reduction from uninjured skin (42%) to week 8 (29%) ( P = 0·02). The OCT attenuation coefficient linked with collagen density and was reduced at week 8 (1·43 mm, P < 0·001). Herovici analysis showed that mature collagen levels were highest in uninjured skin (72%) compared with week 8 (42%, P = 0·04). Fibronectin was greatest at week 4 (0·72 AU) and reduced at week 8 (0·56 AU); and α‐smooth muscle actin increased from uninjured skin (11·5%) to week 8 (67%, P = 0·003). Conclusions: Time‐matched comparison images between haematoxylin and eosin, OCT and HFUS demonstrated that epidermal and dermal structures were better distinguished by OCT. HFUS enabled deeper visualization of the dermis including the subcutaneous tissue. Choice of device was dependent on the depth of scar type, parameters to be measured and morphological detail required in order to provide better objective quantitative indices of the quality and extent of dermal fibrosis. Abstract : What's already known about this topic? Objective studies of the progression of scar formation and the properties of mature scars are necessary in order to evaluate clinical treatment, and for research focused on developing novel methods for management of dermal fibrosis. Optical coherence tomography (OCT) and high‐frequency ultrasound (HFUS) are two known noninvasive techniques that are used effectively for measuring structural and physiological changes in cutaneous tissue. What does this study add? OCT and HFUS are useful tools for noninvasive monitoring of cutaneous fibrosis, enabling quantitative sequential temporal measurements of cutaneous thickness similarly to histology. OCT attenuation coefficient (better in resolution) and HFUS intensity (better in depth) provide an indication of collagen deposition in skin over the course of healing, supported by immunohistochemical analysis. Choice of device is dependent upon wound and scar type, the parameters to be measured and the morphological detail required. Plain language summary available online Respond to this article